Study of Nurse's Philosophy: The Convenient Place to Die Peacefully for Terminal A Patients - Yetti, Krisna; Hariyati, Rr Tutik Sri; Merduati, Rona Cahyantari (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2019)
Background: A patient with terminal illness who will die should be supported and accompanied spiritually for passing their end of life. The spiritual involvement is needed a convenient place since its support will transform a frightening moment to be a peaceful one. Purpose: the aim of the study was describes the convenient place to die peacefully using philosophical approach.Methods: This study used method of an Actual Problem, it is a philosophy reflective study about the assumption of researcher that a patient with terminal illness wants to be accompanied by people who proper to deliver the prayers. In this study, with one participant problems in the place of die are directly exposed, then it is synthesized to solve a fundamental problem. Analysis and synthesis of unsatisfied place to die to be expected can solve the problem. Results: Hospice care is a program or facility which gives specific care for the patient in end of life. It can be said that hospice is a way of care based on philosophy about the end of life. Hospice can be a convenient place to die because there are its staff who will substitute the role of family, in case they experience physical and emotional burden. Conclusion: Hospice can be an alternative of convenient place for patient with dying process and its nursing care can make the process as peaceful as possible